2002
DOI: 10.1023/a:1015574315469
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Different services can meet the needs of different patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
3
5
0
Order By: Relevance
“…In this study, the majority of patients (67.9%) and callers (77.2%) were female, consistent with several other studies of queries to pharmacists [10, 11, 13, 15, 16]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the majority of patients (67.9%) and callers (77.2%) were female, consistent with several other studies of queries to pharmacists [10, 11, 13, 15, 16]. …”
Section: Discussionsupporting
confidence: 91%
“…Callers regularly require quick advice about medications, such as actions to take when doses are omitted or taken accidentally, side effects, whether different medications will interact, or whether medications are safe for patients with certain conditions. Past research has focused on medication advice over the telephone targeting the public or healthcare professionals, provided by clinical pharmacologists, clinical pharmacists, poison specialists and clinical anaesthetists [1016]. Literature around nurses’ provision of telephone based medication advice is, however, lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 20 21 ] The five most common questions types requested from 13-Aban DPIC in comparison with other reports are shown in Table 3 . This pattern is similar to the other reports[ 14 19 20 21 22 ] and it may be showed that therapeutic drug information is one of the main requirements of public in their health matter. In line with previous studies, clients requested the most inquiries were at the age of 18–60 years.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous studies, clients requested the most inquiries were at the age of 18–60 years. [ 11 14 19 22 ] The majority of callers were female that is in agreement with the reports from other parts of the world. [ 11 14 19 22 ]…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation